Reform of the Administrative Sanctions System for Violations of Downstreaming Obligations by Mining Business Permit Holders - Frans Irawan; Lucky Ferdiles (Journal Customary Law, 2026)
This study aims to analyze and reconstruct the administrative sanctions system for enforcing downstreaming obligations in the mineral and coal mining sector, based on Article 33 of the 1945 Constitution and the provisions of Law Number 3 of 2020 and Law Number 6 of 2023. The research method used is a normative juridical approach, with a statutory and conceptual perspective. The results indicate that although downstreaming obligations have been formulated imperatively through the provisions of Article 103 and Article 170 of the Mineral and Coal Mining Law, the existing administrative sanctions system is ineffective due to normative weaknesses such as unclear violation parameters, the lack of measurable success indicators, and the broad discretion of administrative officials. Empirically, weak oversight, inconsistent enforcement of sanctions, and tolerance for violations have created a gap between legal norms and their implementation in the field. Therefore, it is necessary to reconstruct the administrative sanctions system through the implementation of tiered sanctions, the imposition of administrative fines based on state losses, the strengthening of technology-based oversight systems, and the harmonization of regulations between sectors to increase the effectiveness of law enforcement and encourage the success of downstreaming as an instrument of national economic development.